Antidiabetic activity of Ganoderma lucidum polysaccharides F31 down-regulated hepatic glucose regulatory enzymes in diabetic mice. (20th January 2017) - Xiao, Chun; Wu, Qingping; Zhang, Jumei; Xie, Yizhen; Cai, Wen; Tan, Jianbin
Abstract: Ethnopharmacological relevance: Ganoderma lucidum (Lin Zhi) has been used to treat diabetes in Chinese folk for centuries. Our laboratory previously demonstrated that Ganoderma lucidum polysaccharides (GLPs) had hypoglycemic effects in diabetic mice. Our aim was to identify the main bioactives in GLPs and corresponding mechanism of action. Materials and methods: Four polysaccharide-enriched fraction were isolated from GLPs and the antidiabetic activities were evaluated by type 2 diabetic mice. Fasting serum glucose (FSG), fasting serum insulin (FSI) and epididymal fat/BW ratio were measured at the end of the experiment. In liver, the mRNA levels of hepatic glucose regulatory enzymes were determined by quantitative polymerase chain reaction (qPCR) and the protein levels of phospho-AMP-activated protein kinase ( p -AMPK)/AMPK were determined by western blotting test. In epididymal fat tissue, the mRNA and protein levels GLUT4, resistin, fatty acid synthase (FAS) and acetyl-CoA carboxylase (ACC1) were determined by qPCR and immuno-histochemistry. The structure of polysaccharide F31 was obtained from GPC, FTIR NMR and GC–MS spectroscopy, Results: F31 significantly decreased FSG ( P <0.05), FSI and epididymal fat/BW ratio ( P <0.01). In liver, F31 decreased the mRNA levels of hepatic glucose regulatory enzymes, and up-regulated the ratio of phospho-AMP-activated protein kinase ( p -AMPK)/AMPK. In epididymal fat tissue, F31 increased the mRNA levels of GLUT4 but decreased fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC1) and resistin. Immuno-histochemistry results revealed F31 increased the protein levels of GLUT4 and decreased resistin. Conclusion: Data suggested that the main bioactives in GLPs was F31, which was determined to be a β-heteropolysaccharide with the weight-average molecular weight of 15.9 kDa. The possible action mechanism of F31 may be associated with down-regulation of the hepatic glucose regulated enzyme mRNA levels via AMPK activation, improvement of insulin resistance and decrease of epididymal fat/BW ratio. These results strongly suggest that F31 has antidiabetic potential. Graphical abstract: